1993
DOI: 10.1161/01.res.72.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide reverses pulmonary vasoconstriction in the hypoxic and acidotic newborn lamb.

Abstract: We determined whether inhaling low levels of nitric oxide (NO) gas could selectively reverse hypoxic pulmonary vasoconstriction in the near-term newborn lamb and whether vasodilation would be attenuated by respiratory acidosis. To examine the mechanism of air and NO-induced pulmonary vasodilation soon after birth, we measured plasma and lung cGMP levels in the newly ventilated fetal lamb. Breathing at FIO2 0.10 nearly doubled the pulmonary vascular resistance index in newborn lambs and decreased pulmonary bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(56 citation statements)
references
References 38 publications
1
53
0
2
Order By: Relevance
“…Endogenous nitric oxide is present in exhaled air from animals and humans (26). Inhaled nitric oxide gas reverses pulmonary hypertension (27), reverses pulmonary vasoconstriction (28), improves lung function in affected patients and increases ventilation-perfusion ratios (29). In addition, nitric oxide inhibits platelet aggregation (13 -15), platelet (30,31) and leukocyte (16)(17)(18) adhesion on endothelial cells and vascular albumin leakage (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous nitric oxide is present in exhaled air from animals and humans (26). Inhaled nitric oxide gas reverses pulmonary hypertension (27), reverses pulmonary vasoconstriction (28), improves lung function in affected patients and increases ventilation-perfusion ratios (29). In addition, nitric oxide inhibits platelet aggregation (13 -15), platelet (30,31) and leukocyte (16)(17)(18) adhesion on endothelial cells and vascular albumin leakage (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…NO (5-20 ppm) produced an increase in pulmonary artery blood flow, an effect that was equal to the response seen when the Fioz was increased to 1 .O. In all of these studies there was no effect on the systemic circulation, specifically on SVR, and in two studies (14,15) an increase in left-to-right shunting across the ductus occurred during NO inhalation, demonstrating that inhaled NO is a potent selective pulmonary vasodilator in these models.…”
mentioning
confidence: 83%
“…Other clinical trials showed that low-dose iNO given to human newborn infants with persistent pulmonary hypertension reduces the need for extracorporeal membrane oxygenation (41,56). Likewise, experimental animal studies showed that iNO reverses pulmonary vasoconstriction following either hypoxia or prenatal closure of the ductus arteriosus (154,203). The systemic circulation was not dilated in those studies.…”
Section: Evolving Neonatal Cld Leads To Increased Hydrostatic Pulmonamentioning
confidence: 96%